2022
DOI: 10.1177/20571585211070376
|View full text |Cite
|
Sign up to set email alerts
|

Health and work well-being associated with employment precariousness among permanent and temporary nurses: A cross-sectional survey

Abstract: Nursing is at risk of becoming precarious employment with low wages, poor working conditions, heavy workload and underdeveloped career development possibilities. This study aimed to explore employment precariousness, health and work well-being among permanent and temporary practical nurses and registered nurses. The data were collected from Finnish nurses ( n = 5867) using an online questionnaire in autumn 2020. This cross-sectional study was reported by applying the STROBE guidelines. Temporary nurses perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 33 publications
1
12
0
4
Order By: Relevance
“…We found that women were less likely to belong to the cluster "Employee turnover" and more likely to belong to the cluster "Unstable employment" which somewhat supports the earlier findings of precarious work in health care [4,28,40,41]. Women in health care may have somewhat precarious work [42], i.e., they have interruptions in their working careers due to various reasons that could be further investigated in other studies. However, a cautious interpretation could be that both at workplace level but also at societal level, support for career planning within health care or for prevention o interruptions in working should be provided.…”
Section: Discussionsupporting
confidence: 87%
“…We found that women were less likely to belong to the cluster "Employee turnover" and more likely to belong to the cluster "Unstable employment" which somewhat supports the earlier findings of precarious work in health care [4,28,40,41]. Women in health care may have somewhat precarious work [42], i.e., they have interruptions in their working careers due to various reasons that could be further investigated in other studies. However, a cautious interpretation could be that both at workplace level but also at societal level, support for career planning within health care or for prevention o interruptions in working should be provided.…”
Section: Discussionsupporting
confidence: 87%
“…These adverse working conditions, along with underdeveloped career advancement options, lack of in‐service training (Simpson & Simpson, 2019 ) and also nursing's inherent challenges (Kox et al, 2020 ) may change nursing into a job without security (Bodin et al, 2020 ). Precarious working conditions, unfortunately, already hamper the quality of working life in nursing, manifested, in addition to the above‐mentioned issues, as low autonomy, poor control over working times, overwork and high demands (Bayliss‐Pratt et al, 2020 ; Hult et al, 2022 ). Like the participants in this study, many nurses currently intend to leave nursing, though the lack of career development options is only one reason among others.…”
Section: Discussionmentioning
confidence: 99%
“…In considering apprenticeship, we have adopted the definition of positive work experience given by Nilsson et al (2010), which has been tried and tested in different environments (Hult et al, 2022;Wahlstr€ om et al, 2020). It includes three characteristics: job demand, control and social support.…”
Section: Operationalisation Of Variablesmentioning
confidence: 99%